Case Report: GABAergic and Serotoninergic Agents for the Treatment and Prevention of Prolonged Dissociative Stupor - Yoshioka, Daisuke; Iwata, Masaaki; Kaneko, Koichi (Frontiers in Psychiatry, 2021)
Dissociative stupor is a common psychiatric disease without any standard established treatments. The lack of therapeutic options may be due to most patients spontaneously and quickly achieving complete remission. However, since some patients experience multiple relapses and prolonged stupor, investigating potential means for the prevention and treatment of this condition is important. We report the case of a 61-year-old Japanese woman who presented with intermittent dissociative stupor for several months. Despite her prolonged symptoms, the administration of lorazepam, escitalopram, and aripiprazole, which selectively enhance GABAergic and serotoninergic activity, improved her stupor and prevented relapse. These findings suggest that GABA- and serotonin-mediated neural networks may play an important role in the mechanism of dissociative stupor.